India's Taxability of Individual equity Shareholders' dividend income from domestic companies: An analysis of tax implications on dividend income for individual equity shareholders in India (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Since the instituting of the Income Tax Act, 1961, dividend income has been taxed in India underthe heading of other sources. As a result of the many revisions made throughout time, taxation ondividend income has witnessed considerable turbulence. The way dividends are taxed has also changed.A dividend distribution tax was also imposed on domestic corporations whose earnings were either nowbeing distributed to shareholders or had accrued in the previous year and were used to pay dividends tothose shareholders. However, recipient shares are now again subject to tax on the distribution. Thismove would have wreaked havoc on both the stockholders who received their dividends and the firmsthat distribute their income. From 1997 through 2020, this paper looks at the tax treatment of dividendincome from domestic corporations on equity shares in the hands of individual shareholders. Dividendsare paid out to investors in the form of stock or mutual fund shares. Many of their stock and mutual fundassets pay out dividends to investors. That's why a lot of you are worried about whether or not you'llhave to pay taxes on the profits you get from your investments. The taxation of dividend income is thussomething that we should investigate more.